Rose tinted spectacles: Culturally informed differences between Iran and Australia in architect's colour cognition, preference and use. (September 2019) - Motamed, Bahareh; Tucker, Richard
Abstract: This paper investigates if the cultural indoctrination of architects impacts their use of colour in their designs. Here, cultural indoctrination is considered as the process by which an architect's socio-cultural background informs their design ideas and attitudes. Specifically, a survey of 274 architects, architectural academics and postgraduates in Australia and Iran addressed the question: does an architect's cultural background affect their general attitudes to colour and their use of colour when designing and, if so, how? A series of quantitative and qualitative analyses were conducted to answer these questions. The findings reinforce evidence from other studies indicating that colour use is influenced by culture and elucidate for the design community greater understanding about the relationship between culture and colour use in architecture. In particular, it is demonstrated that architects' preferences towards more colourful designs are informed by practice influences; such as contemporary trends and demands, facilitated by new material and representational technologies, for more colourful buildings in our cities. Moreover, although climatic conditions, light intensity, heritage context and local materials were contextual factors influencing colour use both in Iran and Australia, a large difference was found between the two countries on the impact, and especially imposed limitations, of socio-cultural factors on colour cognition, preferences and use. Highlights: Architects' colour orientations are influenced by their cultural indoctrinations. Architects' personal preferences have more influence on colourfulness of buildings than design contexts. Colour bias in Iran and Australia are rooted in contextual and socio-cultural factors.